Contemporary security studies - Collins, Alan 1967- (Oxford University Press, 2013)
This book offers an introduction to Security Studies. It features an impressive breadth and depth of coverage of the different theoretical approaches to the study of security and the ever-evolving range of issues that dominate the security agenda in the 21st Century